Janaka: Aplikasi Android Pembelajaran Menulis Teks Anekdot Kurikulum SMK Pusat Keunggulan - Ahmad Muchson; Didin Widyartono (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This research was carried out with the aim of producing "Janaka," an android application on anecdotal writing material in the vocational school. The method used in this research is ADDIE which consists of five stages analysis, design, development, implementation, and evaluation. This research produces an android application for learning to write anecdotes. The resulting media product has an apk format (android application package) which is a program package that can be run on smartphones with the android operating system that has gone through a series of validations with 87.5% scores from material experts and 74.4% scores from media experts and a trial with the use response value of 81.43% of students and 77.3% of teachers. The material for writing anecdotal texts is divided into three parts: simple research as anecdotal writing materials, writing anecdotes based on facts and data, and turning anecdotes into comic strips. Meanwhile, the media product component as an exercise in writing anecdotal text is divided into an interactive quiz component, an image component, a text and video component for learning materials, and a task collection platform component.